Speech and Music Acoustics, Rhythms of the Brain and their Impact on the Ability to Accept Information - I. V. Pavlov; V. M. Tsaplev (Дискурс)
Introduction. A radical tendency in modern approaches to understanding the mechanisms of the brain is the tendency of some scientists to believe that the brain is a receptor capable of capturing thoughts; the nature of the occurrence of the thoughts themselves, however, is not to be clarified. However, speech expressing thoughts is undoubtedly the result of the work of the brain, so studies of the frequency structure of speech can be the basis for considering the material structure of the brain as a kind of “antenna”. In this approach, the problem of noise protection against the background of the undeniable frequency similarity of speech and music appears to us from somewhat different positions. This study raises the question of how essential the overall height of the musical system is to the perception of music (are there musical systems that are harmful or useful, in terms of their effects on the psyche). This question is also relevant to speech perception.Methodology and sources. The main sources in which the work of the brain and the essence of consciousness are considered from the positions indicated above were for us the work of American and British neurophysiologists and psychiatrists (Sam Parnia, Peter Fenwick). These scientists are studying the phenomena that accompany clinical death, and argue that at these moments the brain functions to the greatest extent as a receiving “antenna”. Assuming that any antenna is to be tuned, we are trying to identify possible ways to “tune” the brain. To do this, we propose to study the frequency characteristics of speech (in the simplest case, when singing vowels in a calm state) for their belonging to a particular musical system, as well as the peculiarities of music perception depending on the musical system (on the height of the note “la”). Varying the frequency characteristics of speech in a particular musical system can be considered, in our opinion, the main way to “tune” the brain. The methodology of the method is based on the use of frequency analysis of sound and the basic provisions of the elementary theory of music.Results and discussion. The main conclusion made by Western psychiatrists is the brain is not an organ of thought, consciousness exists independently from outside, the work of consciousness cannot be explained by the functioning of the brain – it requires a hardware check. If the neural network is an “antenna” that captures thoughts, and its “adjustment” at the physical level can be carried out (and is carried out) through sensory systems (including the hearing organ), the study of the frequency structure of speech will answer a number of important questions, including including related and higher brain functions (insight, creativity). Our experiments (Saint Petersburg Electrotechnical University, FIBS, department of EUT) showed that the influence of the “increased” or “lowered” musical-speech system on brain activity is insignificant. The study revealed the equiprobability of the frequency structure of speech. Since our brain lacks some characteristic set of frequencies – elements of a uniformly temperamental system, it is not necessary to talk about the harmful (or any other noise) effect of the “raised” and “lowered” systems due to deviation from the “internal standard”.Conclusion. In response to the assumptions made by Western experts, we proposed a frequency interpretation of the processes occurring in the brain, which, perhaps, will explain in more detail such phenomena as inspiration, discovery, etc., which occur with minimal activity of consciousness. Despite the limited methods of hardware study of factors that influence the activity of the brain and largely determine its higher functions (for example, creativity), the results of the brain's work in relation to music (both in terms of its creation and in terms of our reaction to it) are quite analyzable , which was shown in this study. The “musicality” of speech is extremely vividly represented in its frequency structure and allows one to reveal, to one degree or another, the features of the brain.